Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s10646-013-1078-5
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of a multi-generation exposure to uranium on Caenorhabditis elegans life parameters and sensitivity

Abstract: The assessment of toxic effects at biologically and ecologically relevant scales is an important challenge in ecosystem protection. Indeed, stressors may impact populations at much longer term than the usual timescale of toxicity tests. It is therefore important to study the evolutionary response of a population under chronic stress. We performed a 16-generation study to assess the evolution of two populations of the ubiquitous nematode Caenorhabditis elegans in control conditions or exposed to 1.1 mM of urani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 55 publications
(57 reference statements)
1
21
0
Order By: Relevance
“…Sixteen-generation studies on the effect of uranium to C. elegans found adaptation to exposure conditions for both exposed and control populations. Observed effects on fecundity were consistent between population treatments, whereas in one of the studies effects on body length showed differential evolution over the exposure duration once maternal effects diminished [15,16].…”
Section: Introductionmentioning
confidence: 77%
“…Sixteen-generation studies on the effect of uranium to C. elegans found adaptation to exposure conditions for both exposed and control populations. Observed effects on fecundity were consistent between population treatments, whereas in one of the studies effects on body length showed differential evolution over the exposure duration once maternal effects diminished [15,16].…”
Section: Introductionmentioning
confidence: 77%
“…Tanaka and Tatsuta 2013) or other pollutants (e.g. Muyssen et al 2005;Agra et al 2010), and involved Daphnia or other organisms (Carriere et al 1994;Goussen et al 2013) as model systems.…”
Section: Evolutionary Potential For Carbaryl Tolerancementioning
confidence: 99%
“…The exposure concentration and internal concentration of the organisms are related throughout time by a toxicokinetic model. The DEBtox models are toxicokinetic-toxicodynamic models (TK-TD) and have proved their reliability in the analysis of data from growth and reproduction tests (Péry et al 2002;Jager et al 2004;Goussen et al 2013). These models also allow estimating a no effect concentration (NEC) which is a threshold for toxicity that does not depend on the time of exposure.…”
Section: Introductionmentioning
confidence: 99%